2010
DOI: 10.5539/ijps.v2n1p44
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Consistency in Purchase Behaviour: Theoretical & Empirical Analyses

Abstract: The fundamental thrust of consistency theories is to enforce equilibrium among one's cognitions. Man seeks haemostatic states among his cognitive elements or avoids conflicting stimuli. He loves the familiar; the unfamiliar is always discomforting and disturbing though common knowledge tells us that actual behaviour turns what seems novel at the pre-decision stage into familiar following series of learning and experience. The Heider's balance theory, Osgood's congruity model and Festinger's cognitive dissonanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…When a dissonance is present, in addition to trying to reduce it, the person will actively avoid situations and information that is likely to increase the the research above, that Festinger [6] has reviewed how to eliminate dissonance that is felt by a person, but the discussion carried out by ] still looks general and requires deeper exploration, so that further research reveal more about the efforts made by a person to reduce feelings of dissonance in various fields of study and with Research on efforts to reduce dissonance, among others, was revealed in the results of Hutagalung's [7] research that for informants who did not experience Dissonance, the form of the communication process was in the form of action not to make any changes to one of the elements of dissonance, such as changing beliefs / beliefs or changing actions. Awa [10], reviewing every individual who finds himself experiencing dissonance, will try to reduce the dissonance in various ways. Hazan and Nasreen [11] review that in the world of marketing, consumers can try various ways to reduce dissonance when deciding to purchase a product.…”
Section: Fig 1 Schematic Of the Theory Of Cognitive Dissonance (Tcd)mentioning
confidence: 99%
“…When a dissonance is present, in addition to trying to reduce it, the person will actively avoid situations and information that is likely to increase the the research above, that Festinger [6] has reviewed how to eliminate dissonance that is felt by a person, but the discussion carried out by ] still looks general and requires deeper exploration, so that further research reveal more about the efforts made by a person to reduce feelings of dissonance in various fields of study and with Research on efforts to reduce dissonance, among others, was revealed in the results of Hutagalung's [7] research that for informants who did not experience Dissonance, the form of the communication process was in the form of action not to make any changes to one of the elements of dissonance, such as changing beliefs / beliefs or changing actions. Awa [10], reviewing every individual who finds himself experiencing dissonance, will try to reduce the dissonance in various ways. Hazan and Nasreen [11] review that in the world of marketing, consumers can try various ways to reduce dissonance when deciding to purchase a product.…”
Section: Fig 1 Schematic Of the Theory Of Cognitive Dissonance (Tcd)mentioning
confidence: 99%
“…These three components are described in literature as, "interrelated, mutually influential and mutually consistent" (Lantos, 2010, p. 504), because consumers need to achieve cognitive consistency (Lantos, 2010). The critical aspect of cognitive consistency is described as, "the valence of the attitude (both direction and strength)," which is, "congruent with the individual's perception of the object-goal relationships" (Awa & Nwuche, 2010;Scott, 1959, p. 220). For example, if a person values a good working environment, and sees that Wal-Mart provides a terrible working environment, then the individual should dislike Wal-Mart.…”
Section: Attitudes Toward Fictional Brands With Parodiesmentioning
confidence: 99%
“…Consumers tend to maintain such "intra-attitude consistency" because without consistency, cognitive dissonance appears (Awa & Nwuche, 2010;Lantos, 2010). For consumers, cognitive dissonance is a state of psychological tension and discomfort caused by the inconsistency among "beliefs, feelings and/or actions" (Lantos, 2010, p. 504).…”
Section: Attitudes Toward Fictional Brands With Parodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Theory of cognitive dissonance is often used to explain how dissatisfaction would lead to high dissonance and the subsequent actions to eliminate it (Thomas, 2010). It elucidates a state of imbalance between one's cognition that results from the contradictory messages, objects, events or experiences (Awa & Nwuche, 2010). In marketing literature, it happens when the products purchased and used do not meet the expectations (Salzberger & Koller, 2010).…”
Section: Theoretical Grounding On Complaint Behaviourmentioning
confidence: 99%